Perlindungan Hukum Terhadap Dokter Dalam Melaksanakan Tindakan Medis (Studi Putusan Pengadilan Negeri Cikarang Nomor 120/Pdt.G/2019/PN Ckr) - Triana, Mida; Cahyo, Cahyo (FOCUS, 2024)
The relationship between doctors and patients involves more than just medical issues; it also includes a contractual relationship known as a therapeutic contract. a therapeutic transaction is a legal relationship between a doctor and a patient in professional medical services, based on competencies aligned with specific skills and expertise in medicine. this study discusses the criminal legal protection for doctors in performing medical procedures on patients and the analysis of the court's decision in case number 120/pdt.g/2019/pn ckr concerning alleged medical negligence. the research method used is normative juridical. the results show that legal protection for doctors is regulated in article 50 of law number 29 of 2004 on medical practice, which states that doctors have the right to obtain legal protection as long as they carry out their duties in accordance with professional standards and operational procedures. furthermore, government regulation number 67 of 2019 also emphasizes that legal protection for health workers is provided as long as they perform their tasks according to these standards. in case number 120/pdt.g/2019/pn ckr, the court declared that the medical actions performed by the doctor were in accordance with the procedure, as evidenced by the presence of informed consent. therefore, actions taken by the doctor that comply with legal regulations cannot be considered unlawful.